The Influence of Retention, Turnover, and Alliance on Process and Outcomes in Rolling Group Psychotherapy for Cocaine Disorder. Issue 4 (1st October 2016) - Pavia, Laura; Di Blasi, Maria; Cinquegrana, Antonia; Scioti, Ernesto; Bussola, Tiziana; Pasinelli, Annaluisa; Cavani, Paola
ABSTRACT: A longitudinal repeated measures design was used to investigate the influence of treatment retention, and membership turnover on individual outcomes, and the relationship between individual-level and group-level therapeutic alliance in rolling group psychotherapy for individuals with cocaine abuse disorder. Eighteen patients were studied; data were collected prior to therapy and then monthly for 24 months. Patient outcomes and process were assessed. Improvements in symptoms and psychological functioning were associated with retention in psychotherapy. Membership turnover had a negative influence on symptoms. Development of an individual alliance was affected by the development of group-level therapeutic alliance, but not by time spent in therapy.